[OP.8C.08] INTERACTION BETWEEN PERIPHERAL ALPHA-ADRENERGIC RECEPTORS AND NEURONAL NITRIC OXIDE SYNTHASE. (September 2016) - Khan, F.; Jiang, S.; Farukh, B.; Brett, S.; Shah, A.M.; Chowienczyk, P.
Abstract : Objective: Vascular tone is influenced by release of norepinephrine (NE) from sympathetic nerves and by nitric oxide (NO) released from perivascular neuronal NO synthase (nNOS). nNOS appears a more important physiological determinant of vascular tone than endothelial NO synthase (eNOS), particularly when stimulated by stress. Thus vascular tone is determined mainly by the balance of the two neurally released mediators, NE tending to constrict and NO to dilate vascular smooth muscle. Indirect observations suggest there may be cross-talk between peripheral α-adrenergic receptors and nNOS signalling. Design and method: We therefore examined local forearm vasodilator responses to intra-brachial artery infusion of the non-selective α-adrenergic antagonist phentolamine in the presence and absence of S-methyl-L-thiocitrulline (SMTC), a specific inhibitor of nNOS. Normotensive participants (n = 12, 7 female, mean ± SD age 33 ± 13 years) were studied on two separate occasions in a two-visit single-blind, cross-over study, with each visit separated by at least 7 days. SMTC (0.2 μmol/min, a dose that inhibits vasodilation to mental stress but not to other NO donors or to calcium channel antagonists) on one visit and saline vehicle on the other were co-infused with a rising dose infusion of phentolamine (10, 30 and 100 μg/ml/min). Results: Phentolamine increased forearm blood flow less (from 3.39 ± 0.58 to 6.01 ± 1.10 ml/min/100 ml) when co-infused with SMTC compared to saline vehicle (increase from 3.37 ± 0.45 to 8.74 ± 1.16 ml/min/100 ml, P < 0.05 for difference in blood flow response). Conclusions: These data suggest that peripheral α-adrenergic receptors inhibit nNOS activation, an action likely to potentiate vasoconstrictor responses and to oppose antithrombotic and antiplatelet effects of nNOS-derived NO and which may contribute to nNOS dysfunction in hypertension and in other conditions associated with increased sympathetic activation.